2022
DOI: 10.3390/nu14245227
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Contributes to Inflammation in Patients with IBS via Complement Component 3 and C-Reactive Protein

Abstract: Irritable Bowel Syndrome (IBS) is usually a lifelong state that disturbs the digestive system. IBS has been linked to low-grade inflammation and the release of inflammatory mediators into the bloodstream. This could be associated with the degree of obesity presented by patients with IBS. Reports imply that IBS is more frequent in obese patients than in the overall population, with a prevalence of up to 31%. Here, we evaluated the serum levels of immunological and inflammation molecules and their correlation wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The gastrointestinal reflexes may be impacted by these processes 57 , and obese individuals with IBS were shown to have higher levels of inflammatory biomarkers than controls. 58 Previous results proved that smoking inhibits the development of IBS by decreasing gut mucosal inflammation and delaying gastrointestinal tract motility 59 ; this could be linked to the fact that in our investigation, smokers with greater BMI had considerably reduced risks of developing IBS. According to a study 3 , severe sleeplessness in non-smokers was substantially associated with a greater likelihood of developing IBS.…”
Section: Discussionmentioning
confidence: 50%
“…The gastrointestinal reflexes may be impacted by these processes 57 , and obese individuals with IBS were shown to have higher levels of inflammatory biomarkers than controls. 58 Previous results proved that smoking inhibits the development of IBS by decreasing gut mucosal inflammation and delaying gastrointestinal tract motility 59 ; this could be linked to the fact that in our investigation, smokers with greater BMI had considerably reduced risks of developing IBS. According to a study 3 , severe sleeplessness in non-smokers was substantially associated with a greater likelihood of developing IBS.…”
Section: Discussionmentioning
confidence: 50%
“…A prospective cohort study conducted in Norway showed that weight loss can alleviate IBS symptoms [ 73 ]. In addition, inflammatory processes have been linked to IBS, these processes can alter the gastrointestinal reflexes [ 74 ] and higher levels of inflammatory biomarkers were detected in obese patients with IBS in comparison with controls [ 75 ]. However, smokers with higher BMI in our study were significantly associated with lower odds of having possible IBS; this finding can be related to the hypothesized role of cigarette smoking in preventing the development of IBS by reducing the gut mucosal inflammation [ 76 ] and slowing the gastrointestinal tract motility [ 77 ].…”
Section: Discussionmentioning
confidence: 99%